(untitled) - O’Driscoll, Gerard (Hoboken, N.J., 2008)
With a focus on changing job tasks and knowledge requirements for professionals, this book enables readers to meet the demands of designing, implementing, and supporting end-to-end IPTV systems. Additionally, it examines IPTV technical subjects that are not included in any other single reference to date: Quality of Experience (QoE), techniques for speeding up IPTV channel changing times, IPTV CD software architecture, Whole Home Media Networking (WHMN), IP-based high-definition TV, interactive IPTV applications, and the daily management of IPTV networks.
Keywords: Internet television,Truyền hình Internet